CHANGES IN TEMPERATURE REGIME AND PRECIPITATION REGIME OF WARM AND COLD PERIODS IN VARIOUS CLIMATIC ZONES OF THE NORTH CAUCASUS REGION - B. A. Ashabokov; L. M. Fedchenko; L. A. Kesheva; N. V. Teunova (Наука. Инновации. Технологии)
Introduction . Climate change is currently viewed by many states as one of the most important global challenges of our century and is considered a serious threat to sustainable development . This paper analyzes the changes in the temperature and precipitation regime in the North Caucasian region during the warm and cold periods for 1961-2019 Results of the study and their discussion The climatic features of the territory of the North Caucasus region are determined by a number of factors, the main of which are the Caucasus Mountains, which serve as a climatic divide between the temperate and subtropical zones In the study of climate change in the North Caucasus region, data from time series of temperatures in the surface layer of the atmosphere and atmospheric precipitation in the warm and cold seasons of the period 1961-2019 were used The obtained time series were investigated by methods of mathematical statistics and supplemented with linear trends characterizing the trend of the value under consideration . Research results and discussion Average temperatures and precipitation were calculated for the cold period, which includes October-December of the previous year and January-April of the next year, and the warm period, from May to September, for 11 weather stations located in 4 climatic zones of the region Further, the obtained values were averaged within each climatic zone Climatic norms (average 1961-1990) were determined for each climatic zone in warm and cold periods In all climatic zones in the cold and warm periods, an excess of the temperature climatic norm is observed, with the exception of the high-mountain zone in the cold period For the amount of precipitation, the warm period is characterized by a decrease in the amount of precipitation, except for the mountainous zone In the cold season, an increase in precipitation is observed in all climatic zones The obtained time series were investigated by the methods of mathematical statistics and supplemented with linear trends characterizing the trend of the value under consideration for the period 1961-2019 Trends were calculated by the well-known least squares method . The strength of the trend, its statistical significance, was estimated by the value D (%), the contribution of the trend to the explained variance: D = (R2) 100% At the 5% level, the trend is statistically significant for the coefficient of determination above R2 = 0 065 Conclusions . In all climatic zones of the North Caucasus region in the period 1961-2019 . There was a statistically significant increase in average temperatures, both in cold and warm periods, with the exception of the cold period in the high mountain zone Analysis of precipitation for the period under consideration in various climatic zones of the region showed that changes in precipitation amounts combined negative and positive statistically insigniicant trends Negative trends were mainly observed during the warm period, except for the mountainous zone, where there was a slight positive trend